Hos 10,9 - Söhne der Ungerechtigkeit? - Schütte, Wolfgang (Biblische Notizen, 2009)
Hos 19,9 hwl[ ynb / sons of Alwa can be understood as a reference to people of Edom as elsewhere in OT, not as a single reference to a hebrew word like LXX ἀδικία / „wickedness“.